KEARIFAN LOKAL POLA TANAM TUMPANGSARI DI JAWA TIMUR - Eko Setiawan (Universitas Trunojoyo Madura, 2009)
This study aims to determine the planting pattern intercropping systems done by the community in the Province of East Java based on the local wisdom of farmers is done at the end of the rainy season. The study was conducted in East Java Province which covers several districts are: District Bangkalan, Sampang, Pamekasan, Sumenep, Lamongan, Kediri, Sidoarjo, Gresik, and Probolinggo. Research conducted at the end of the rain season in May 2009. Data obtained from the survey with a combination of record intercropping systems, which is owned by farmers from the local wisdom of the local community. From this data further grouped according to the number of plants and combined according to the type of trees. The results of research local wisdom of pattern intercropping systems inEast Java obtained 28 types of crops are grown by farmers. There are 80 combinations of model plants, where there are a number of similarities between the model combinations of plant area with the other farmers of 31% (25 models). While the rest of 69% (55 models) a combination of the plant model a different with other farmers.